Diversity of arbuscular Mycorrhizal fungi isolated from Ha Noi maize cultivated soil - Thi Dung, Luu; Thi Hoang Yen, Le; Thi Le Quyen, Le; Van Hop, Duong (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2S, 2017)
A total 576 AMF spores were isolated from 15 maize cultivated soil samples collected in Ha Noi. Spores were analyzed under microscope at 200 × magnifications and divided in groups in relation to morphological characteristics as shape, size, colour, wall structures. As a results, there are 8 genera, 15 species of AMF were isolated: Acaulospora (3 species): Acaulospora capsicula, Acaulospora mellea, Acaulospora rehmii ; Cetraspora (1 species): Cetraspora pellucid ; Dentiscutata (2 species ): Dentiscutata nigra, Dentiscutata reticulate ; Gigaspora (4 species): Gigaspora albida, Gigaspora decipiens, Gigaspora gigantea, Gigaspora margarita; Glomus (2 species): Glomus ambisporum, Glomus multicaule; Racocetra (1 species): Racocetra gregaria; Rhizophagus (1 species): Rhizophagus clarus ; Septoglomus (2 species): Septoglomus constrictum, Septoglomus deserticola. Among them, Dentiscutata , Racocetra, Rhizophagus and Septoglomus are the first time reported in Viet Nam. Among them, 4 genus: Dentiscutata , Racocetra, Rhizophagus and Septoglomus were the first time reported in Viet Nam. Acaulospora , Dentiscutata , Gigaspora and Glomus were the dominant genera, and Gigaspora decipiens, Gigaspora gigantean and Glomus multicaule were the dominant species in maize cultivated Ha Noi soil. Fungal spore density ranged from 9.5 to 102 per 100 g dry soil (mean = 38.4) and species richness ranged from 1-7 (mean = 3.3).